Empirical Analysis of High-Inflation Episodes in Argentina, Brazil, and Israel. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1988)
Although accommodative policies and widespread indexation may account for the persistence of high inflation, they cannot explain changes in the inflation rate. This paper examines the causes of such changes for the high-inflation episodes immediately preceding the recent 'heterodox' attempts at stabilization in Argentina, Brazil, and Israel. An attempt is made to distinguish between the 'fiscal' and 'balance of payments' views of the causes of high inflation by computing historical decompositions of these episodes based on vector autoregressions. In all three cases, the results indicate that nominal exchange rate shocks played the dominant role in triggering an acceleration of inflation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet